el-Muhatasaru’l-muhtâc ileyhi târîhu’l-hâfız Ebî Abdillâh Muhammed b. Sa’îd b. Muhammed b. ed-Dübeysî - 880-01 Zehebî, 1274-1348. (Bağdat)
2 kitap 1 ciltte (1. kitap 30 sayfa, [2] sayfa tıpkıbasım, 286 sayfa ; 2. kitap 46 sayfa)